Institutional change and agricultural land use in transition countries: Understanding institutional constraints of farmers' decision making - Zarema Akhmadiyeva (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2022)
Depending on multiple factors and regional characteristics, the area of agricultural land fuctuates with varying scale and speed. These fuctuations generally occur as a result of changes in a way individuals use their land. Human activities, such as agricultural expansion, intensifcation, or land abandonment, play a signifcant role not only in maintaining economic well-being and food security but also in the transformation of landscapes, environmental conditions, and biodiversity. Environmental and socio-economic factors are claimed to be the dominant determinants of land use change; however, the impact of institutional change cannot be neglected. Post-Soviet and allied countries introducing market-oriented reforms during the last three decades demonstrated profound fuctuations in the area of cultivated land. Simultaneously, this period was associated with substantial institutional shifts in the agricultural sector of transition economies. Despite the adoption of similar reforms after 1990, these countries have been following discrepant trajectories in agricultural development. The sources of discrepancies were not only unequal initial institutional conditions but also land reforms that were implemented partially or remained written only on the paper without entering into force. In order to investigate how institutional change infuences land use in transition economies, this dissertation considers an analysis of land tenure settings at cross-country and individual levels. – – In Abhängigkeit von mehreren Faktoren und regionalen Merkmalen schwankt die landwirtschaftliche Nutzfäche mit unterschiedlichem Umfang und Geschwindigkeit. Diese Schwankungen treten im Allgemeinen aufgrund von Änderungen in der Art und Weise auf, wie Menschen ihr Land nutzen. Menschliche Aktivitäten wie die Expansion, Intensivierung oder Aufgabe von Land in der Landwirtschaft spielen nicht nur eine wichtige Rolle bei der Aufrechterhaltung des wirtschaftlichen Wohlergehens und der Ernährungssicherheit, sondern auch bei der Veränderung von Landschaften, Umweltbedingungen und biologischer Vielfalt. Es wird behauptet, dass Umwelt- und sozioökonomische Faktoren die dominierenden Determinanten der Landnutzungsänderung sind, wobei die Auswirkungen des institutionellen Wandels jedoch nicht vernachlässigt werden können. Die postsowjetischen und alliierten Länder, die in den letzten drei Jahrzehnten marktorientierte Reformen eingeführt haben, zeigten tiefgreifende Schwankungen in den kultivierten Landfächen. Gleichzeitig war dieser Zeitraum mit erheblichen institutionellen Veränderungen im Agrarsektor der Transformationsökonomien verbunden. Trotz der Verabschiedung ähnlicher Reformen nach 1990 haben diese Länder unterschiedliche Wege in der landwirtschaftlichen Entwicklung eingeschlagen. Die Ursachen für Diskrepanzen waren nicht nur ungleiche institutionelle Anfangsbedingungen, sondern auch Landreformen, die nur teilweise umgesetzt oder lediglich auf dem Papier festgehalten wurden. Um zu untersuchen, wie institutionelle Veränderungen die Landnutzung in Transformationsökonomien beeinfussen, wird in dieser Dissertation eine Analyse von Landbesitzbedingungen auf länderübergreifender und individueller Ebene durchgeführt.
urn:nbn:de:gbv:3:2-925468
Keywords: 330; land rights; land intensification; tenure security; land abandonment; institutional change; transition economies; perceived land rights; theory of planned behaviour; law enforcement